Nanoscale probing of the lateral homogeneity of donors concentration in nitridated SiO2/4H–SiC interfaces. (21st June 2016) - Fiorenza, Patrick; Di Franco, Salvatore; Giannazzo, Filippo; Roccaforte, Fabrizio
Abstract: In this paper, nanoscale resolution scanning capacitance microscopy (SCM) and local capacitance–voltage measurements were used to probe the interfacial donor concentration in SiO2 /4H–SiC systems annealed in N2 O. Such nitrogen-based annealings are commonly employed to passivate SiO2 /SiC interface traps, and result both in the incorporation of N-related donors in SiC and in the increase of the mobility in the inversion layer in 4H–SiC MOS-devices. From our SCM measurements, a spatially inhomogeneous donor distribution was observed in the SiO2 /4H–SiC system subjected to N2 O annealing. Hence, the effect of a phosphorus implantation before the oxide deposition and N2 O annealing was also evaluated. In this case, besides an increased average donor concentration, an improvement of the lateral homogeneity of the active doping was also detected. The possible implications of such a pre-implantation doping of the near-interface region on 4H–SiC MOS-devices are discussed.